Correção cirúrgica do estrabismo horizontal em portadores de alta miopia - Ejzenbaum, Fábio [UNIFESP] (2001)
Purpose: To analyze results of correction of horizontal strabismus surgical in high myopia patients. Methods: A retrospective chart review of 24 patients with esotropia and high myopia (greater than -6.00 spherical diopters) and 17 patients with exotropia and high myopia compared with their control groups. Deviation between 10delta of esotropia and 10delta of exotropia was considered a surgical success. Results: We noticed a high incidence of bad results among the esotropic patients with high myopia. Conclusion: There is a tendency of bad results among the esotropic patients with myopia greater than -6.00 when compared with patients with spherical refractive error between -0.75 and +3.50.